Molecular characterization of Brazilian wild-type strains of bovine respiratory syncytial virus reveals genetic diversity and a putative new subgroup of the virus - Raquel Arruda Leme; Alais Maria Dall Agnol; Luciana Carvalho Balbo; Fernanda Louise Pereira; Flávia Possatti; Alice Fernandes Alfieri; Amauri Alcindo Alfieri (Veterinary Quarterly, 2020)
Background Bovine orthopneumovirus, formerly known as bovine respiratory syncytial virus (BRSV), is frequently associated with bovine respiratory disease (BRD). Aim To perform the molecular characterization of the G and F proteins of Brazilian wild-type BRSV strains derived from bovine respiratory infections in both beef and dairy cattle. Materials and Methods Ten BRSV strains derived from a dairy heifer rearing unit (n = 3) in 2011 and steers of three other feedlots (n = 7) in 2014 and 2015 were analyzed. For the BRSV G and F partial gene amplifications, RT-nested-PCR assays were performed with sequencing in both directions with forward and reverse primers used. Results The G gene-based analysis revealed that two strains were highly similar to the BRSV sequences representative of subgroup III, including the Bayovac vaccine strain. However, the remaining seven Brazilian BRSV strains were diverse when compared with strains representative of the BRSV I to VIII subgroups. The central hydrophobic region of the Brazilian BRSV G gene showed the replacement of conserved cysteines and other residues of importance to antibody reactivity. The deduced F gene amino acid sequences from the Brazilian BRSV strains showed changes that were absent in the representative sequences of the known subgroups. Viral isolation on the nasopharyngeal swab suspensions failed to isolate BRSV. Conclusion Results suggest that these strains represent a putative new subgroup of BRSV with mutations observed in the immunodominant region of the G protein. However, further studies on these Brazilian BRSV strains should be performed to establish their pathogenic potential.